Beyond Allylic Alkylation: Applications of Trost Chemistry in Complex Molecule Synthesis. Issue 5 (29th January 2021) - Tracy, Jacob S.; Kalnmals, Christopher A.; Toste, F. Dean
Abstract: During his fifty‐five year tenure, Prof. Barry M. Trost has made countless advancements in the fields of synthetic method development and complex molecule total synthesis. In addition to his well‐known contributions in the areas of allylic alkylation and transition metal‐catalyzed cycloisomerization reactions, Prof. Trost has developed many other useful synthetic methods as well. Although less prominent than some of his hallmark transformations, these reactions are no less significant and have enjoyed widespread adoption by the synthetic community. This review highlights many of these unsung processes – including several reduction/oxidation reactions, metal‐catalyzed alkene‐alkyne and alkyne‐alkyne couplings, phosphine‐catalyzed redox isomerizations, and methods for determining absolute stereochemistry – and their utility in the total synthesis of natural products, pharmaceuticals, and other complex bioactive molecules. Abstract :